Pelatihan Learning Mangemen System (LMS) pada SMA Negeri 3 Lintong Nihuta - Mendarissan Aritonang; Yusuf Ijonris; Erika Nora Simamora; Jhoni Maslan Hutapea; Posma Lumban Raja; Elisabeth Sitepu; Nurlaidy J. Simamora; Fati Gratianus Nafiri Larosa; Nettina Samosir; Veraci Silalahi; Imelda Sri Dumayanti Sinaga; Pebrin Lumban Toruan; Jon Kristiansah Silaban; Sartika Mariani Simanjuntak (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
The development of information technology has accelerated digital transformation in education, including the utilization of Learning Management Systems (LMS) as learning media. However, the understanding and skills of teachers and students in using LMS platforms still need improvement, particularly at SMA Negeri 3 Lintongnihuta. Therefore, the Faculty of Computer Science, Universitas Methodist Indonesia Medan, conducted a Community Service Program in the form of Moodle LMS training for teachers and students. The activity was implemented through training and mentoring methods, including material presentations, Moodle demonstrations, hands-on practice, discussions, and evaluations. The results showed an improvement in participants’ understanding and skills in managing digital classrooms, uploading learning materials, administering assignments, and utilizing Moodle’s assessment features. In addition to enhancing technical competencies, the program also promoted digital literacy and increased awareness of the importance of digital transformation in education. Teachers and students became better prepared to utilize technology as an effective, interactive, and flexible learning tool. Therefore, Moodle LMS training can be considered an effective strategy for supporting the development of digital learning environments in schools.